Indigenous and Trans-Systemic Knowledge Systems (ᐃᐣdᐃgᐁᓅᐢ ᐠᓄᐤᐪᐁdgᐁ ᐊᐣd ᐟᕒᐊᐣᐢᐢᐩᐢᑌᒥᐨ ᐠᓄᐤᐪᐁdgᐁ ᐢᐩᐢᑌᒼᐢ) - Marie Battiste; Sa’ke’j Henderson (Engaged Scholar Journal, 2021)
This special issue addressing the theme of “Indigenous and Trans-Systemic Knowledge Systems” seeks to expand the existing methods, approaches, and conceptual understandings of Indigenous Knowledges to create new awareness, new explorations, and new inspirations across other knowledge systems. Typically, these have arisen and have been published through the western disciplinary traditions in interaction and engagement with diverse Indigenous Knowledge systems. Written by Indigenous and non-Indigenous scholars, and in collaborations, the contributions to this issue feature the research, study, or active exploration of applied methods or approaches from and with Indigenous Knowledge systems as scholarly inquiry, as well as practical communally-activated knowledge. These engagements between Eurocentric and Indigenous Knowledges have generated unique advancements dealing with dynamic systems that are constantly being animated and reformulated in various fields of life and experiences. While these varied applications abound, the essays in this issue explore the theme largely through scholarly research or applied pedagogies within conventional schools and universities. The engagement of these distinct knowledge systems has also generated reflective, immersive, and transactional explorations of how to foster well-being and recovery from colonialism in Indigenous community contexts.